Erbium ion implantation into LiNbO3, Al2O3, ZnO and diamond – measurement and modelling – an overview. Issue 32 (9th August 2022) - Cajzl, Jakub; Nekvindová, Pavla; Macková, Anna; Varga, Marian; Kromka, Alexander
Abstract : The presented overview deals with an experimental and theoretical study of erbium ions incorporated in crystal materials of LiNbO3, Al2 O3, ZnO and diamond for use in photonics and optoelectronics. Abstract : The presented overview deals with the study of the luminescence properties of lanthanide ions incorporated into different dielectric crystalline materials for use in photonics and optoelectronics. From the crystalline materials, non-centrosymmetric hexagonal crystals of LiNbO3, Al2 O3 and ZnO, together with the centrosymmetric cubic crystal of diamond, were chosen. The above-mentioned materials represent a certain cross-section through various crystal structure geometries with different internal bonding of atoms which represent different crystal vicinity for the incorporated Er ions. During more than ten years of our research, each of the crystals was doped with erbium ions and the resulting structural and luminescence properties were studied in detail and compared between the mentioned crystalline materials to find similar behaviour for erbium ions in the different crystalline materials. To better understand the incorporation of erbium in the studied crystalline materials, theoretical simulations of different erbium-doped crystal models were carried out. In the calculations, cohesive energies of the structures and erbium defect-formation energies were compared in order to find the most favourable erbium positions in the crystals. Also, from the geometry optimization calculations, the optimal geometry arrangements in the vicinity of erbium ions in different crystals were studied and visualized. The results of the theoretical simulations confirmed the experimental results – i.e., from all the theoretical erbium-doped crystal models, the most stable structures contained erbium in the substitutional positions with octahedral oxygen coordination.